Análise do desempenho estrutural de vigas com perfil I em madeira colada, utilizando três diferentes tipos de adesivos - Tomé, Karina Taiza (2022)
Researches in several sectors has focused on replacing raw materials from fossil fuels with materials of natural and renewable origin. In this sense, studies focused on the use of timber in civil and agricultural construction have been encouraged and developed. Timber can be used as a definitive structure, examples of beams and pillars, or temporary structures, as in struts and forms. Still, the study of composite elements in timber has received significant attention from industries and researchers. Therefore, the present study aimed to produce and evaluate the structural performance of I-beams of glued laminated timber and made of Pinus sp. timber, with three different types of adhesives, namely: two-component vegetable oils-based adhesive. The timber characterization was carried out to obtain its physical and mechanical properties, as well as preliminary tests to define the gluing pressure and consumption for the use of PUR and epoxy adhesive. Through the results found in the tests and statistical analysis, it was defined that the PUR adhesive consumption would be 250 g/m² and bonding pressure of 0.7 MPa; for the epoxy adhesive, consumption of 300 g/m² and pressure of gluing of 1.0 MPa. For the vegetable oil-based adhesive, a consumption of 300 g/m² and a pressure of 0.8 MPa were used, based on studies already carried out. Twenty one beams were made with an upper flange of 8.3 cm and a lower flange of 5.2 cm in width and 2 cm in thickness and a web with 12 cm in height and 2 cm in thickness. A length of 2.50 m was adopted, with a free 2.30 m span between the supports. As for the strengths, the beams glued with vegetable oil-based adhesive had a higher average rupture load of 20.45 kN, while the beams glued with PUR reached 18.82 kN and the beams glued with epoxy adhesive had an average of 16.40 kN. As for stiffness, the structures reached the normative limits for total loads in the order of 3 kN for allowable deflection of L/350 and 5 kN for normative deflection of L/200. In addition, it was observed that the beams glued with castor oil had higher average stiffness when compared to the other adhesives. Regarding the theoretical displacements of these arrows, the beams showed higher values. As for the statistical analysis of the strengths and limit deflections, it was observed that there was no significant difference at the 5% level between the adhesives.